Can Nonfibrotic Nonalcoholic Steatohepatitis Be Effectively Identified by Supersonic Shear Imaging? - Jiajia Yang; Liwu Lin; Ensheng Xue; Dengke Hong; Yan Yang; Meifang Xu; Zhikui Chen (Analytical Cellular Pathology)
Supersonic shear imaging (SSI) is a relatively new technique to measure the elasticity of target tissues based on the shear wave propagation. The aim of this study was to evaluate the value of SSI in discriminating nonfibrotic nonalcoholic steatohepatitis (NASH) from the less severe nonalcoholic fatty liver disease (NAFLD), NASH with fibrosis, and the normal liver, as well as the relationship between various NAFLD pathologic or biochemical findings and SSI liver elasticity. Rabbits with NAFLD of different degrees were subjected to SSI for liver elasticity measurement. Plasma was collected for biochemical examinations, and liver tissues were harvested for pathologic assessment. Results showed that liver elasticity of rabbits with nonfibrotic NASH was significantly different from that of rabbits with simple steatosis, borderline, NASH with fibrosis, and normal liver (P<0.05) and the areas under the receiver operating characteristic curve of SSI for predicting nonfibrotic NASH and NASH with fibrosis were 0.997 and 0.967, respectively, and the optimal cutoff values were 10.17 kPa and 12.82 kPa, respectively. Multivariate analysis showed that only fibrosis and inflammation were the independent factors affecting liver elasticity of NAFLD (P≤0.001), while inflammation, steatosis, and ballooning degeneration were all independently related to liver elasticity in rabbits without fibrosis (P<0.01). In addition, alanine aminotransferase was the only biochemical factor independently related to liver elasticity (P≤0.001). Our results indicate that SSI can effectively identify nonfibrotic NASH in rabbits based on the difference in liver elasticity and the difference is related to the various pathologic changes, including fibrosis, inflammation, steatosis, and ballooning degeneration.